Characteristics of Raw Domestic Sewage for Basrah City - Mohammed, Risala A.; Mohammed, Alia A.; Hassan, Ibtihal H. (Basrah Journal for Engineering Sciences, 2012)
The analysis of raw domestic sewage has a greater importance for design of an effective and economic rational sewage treatment. The objectives of this study are to determine the chemical, physical and Biochemical characteristics of raw domestic sewage for Basrah city. Results show that; the strength of Basrah raw domestic sewage can be classified as a strong strength concentration wastewater due to high levels of organic loading rate BOD5 , COD. Also, it can be seen a very high concentrations of TDS , CL- and increasing in EC levels above the typical limits due to the salinity of domestic water supply in Basrah. High concentrations of oil and grease were found as result of misuse of the sewerage system. While the values of pH, temperature, nutrients and the number of FC are within the typical acceptable limits.